2013
DOI: 10.1186/1755-1536-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Secreted protein acidic and rich in cysteine (SPARC) is upregulated by transforming growth factor (TGF)-β and is required for TGF-β-induced hydrogen peroxide production in fibroblasts

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a poorly understood progressive disease characterized by the recurrent damage of alveolar epithelial cells as well as inappropriate expansion and activation of fibroblasts resulting in pronounced extracellular matrix (ECM) deposition. Although recent studies have indicated the involvement of secreted protein acidic and rich in cysteine (SPARC), a matricellular protein regulating ECM deposition, in the pathogenesis of fibrosis, factors regulating SPARC expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…SPARC-deficient mice exhibit tissue repair defects manifesting as delayed formation of granulation tissue and diminished ECM production [46]. SPARC is also involved in idiopathic pulmonary fibrosis through activation by TGFβ [47]. Inhibition of SPARC attenuates the pro-fibrotic effect of TGFβ [48].…”
Section: Matrix Deposition and Dynamics In The Wound Healing Cascadementioning
confidence: 99%
“…SPARC-deficient mice exhibit tissue repair defects manifesting as delayed formation of granulation tissue and diminished ECM production [46]. SPARC is also involved in idiopathic pulmonary fibrosis through activation by TGFβ [47]. Inhibition of SPARC attenuates the pro-fibrotic effect of TGFβ [48].…”
Section: Matrix Deposition and Dynamics In The Wound Healing Cascadementioning
confidence: 99%
“…Sangaletti et al proposed a differential function of SPARC in fibroblasts and macrophages in a model of bleomycininduced lung fibrosis; using SPARC depleted mice and bone marrow chimeras, they found that SPARC expression by fibroblasts was required to induce collagen deposition, while SPARC depletion from macrophages caused exacerbated inflammation and fibrosis because of their inability to downregulate TNF-a production (92). In another study, SPARC was required for H2O2 production by lung fibroblasts after TGF-β1 treatment, while SPARC knock-down in fibroblasts attenuated epithelial cell injury in a co-culture system (93). In liver fibrosis SPARC is upregulated in activated HSCs and mediates their migration towards TGF-β1 and TGF-β1 secretion (94).…”
Section: Sparcmentioning
confidence: 99%
“…Many articles reported that SPARC acted as a regulator of cancer cell metastasis and carcinogenesis . In fibroblasts, SPARC was upregulated by TGF‐β1 and required for hydrogen peroxide production . SPARC was overexpressed in idiopathic pulmonary fibrosis fibroblasts and conferred an apoptosis‐resistant phenotype .…”
Section: Introductionmentioning
confidence: 99%